The origins of modern Polish democracy / edited by M.B.B. Biskupski, James S. Pula, and Piotr J. Wróbel. - Biskupski, Mieczysław B.; Pula, James S., 1946-; Wróbel, Piotr J. (Ohio University Press Polish and Polish-American studies series., 2010)
""This important book, to which mane of the leading scholars of the subject have contributed, provides a clear and accessible account of the evolution of Polish democratic thought and of the aspirations of the Polish people for a democratic political system from the 1863 January Uprising to the present day. It fills a long-felt need in the scholarship on this topic."-Antony Polonsky, Albert Abramson Professor of Holocaust Studies, United States Holocaust Memorial Museum and Brandeis University" ""The presentation of Polish democratic traditions and aspirations in this valuable study helps us understand not only the past but also the present. Following an insightful introduction, nine outstanding Polish, Canadian, and American historians concentrate on developments in the nineteenth and twentieth centuries. Their views, occasionally controversial, make for rewarding and stimulating reading. A most welcome addition to the field."-Piotr S.